Control of guanine-rich DNA secondary structures depending on the protease activity using a designed PNA peptide. Issue 7 (18th December 2014) - Usui, Kenji; Okada, Arisa; Kobayashi, Keita; Sugimoto, Naoki
Abstract : A regulation system for DNA secondary structure formation of G-rich sequences using a designed PNA peptide exhibiting an enzyme-responsive functionality, depending on the protease activity was constructed. Abstract : We constructed a regulation system for DNA secondary structure formation of G-rich sequences using a designed PNA peptide exhibiting an on-to-off switching functionality, depending on the protease activity. This study introduces the new concept of a simple and powerful system for regulating quadruplex-related important biological events.